Optimal age for screening lumbar osteoporosis in celiac disease - Azita Ganji; Sara Samadi; Masoumeh Sadeghi; Nikta Baniasadi; Vahid Ghavami; Reza Ganji (Scientific Reports)
Abstract Osteoporosis is a common and important predictor of poor outcomes in celiac disease (CD), which puts many patients at risk of further fractures. Our objective was to evaluate the stratification of osteoporosis odds in CD patients based on their age, aiming to determine the optimal timing for initiating osteoporosis screening in this population.This cross-sectional study was performed on adult CD patients who were referred to the Celiac Clinic Center between 2015 and 2020. The exclusion criteria included individuals with endocrine disorders, corticosteroid use, smoking habit, post-menopausal women, and patients younger than 25 years old. Intestinal pathology, bone mineral density (BMD), TGA-IgA serum level, and serum vitamin D were assessed at the time of diagnosis. A total of 199 CD patients, who underwent lumbar densitometry at the time of their diagnosis, were included in the study with a mean age of 39.14 ± 8.99 years old. Osteoporosis was observed in 23.6% patients, of whom 25.5% were men and 74.5% were women. The results revealed a notable disparity across the four age groups. After accounting for potential confounding factors in multivariate analysis in fully adjusted model, our findings demonstrated that individuals between the ages of 45 and 55 had 22% higher odds of developing lumbar osteoporosis (odds ratio, 1.22; 95% CI, 1.02–1.45) compared to those aged 25–35. Individuals with CD are at an increased risk of developing lumbar osteoporosis in middle age. Therefore, it is recommended to begin BMD screening at age 45 and beyond. This recommendation further emphasizes the importance of receiving appropriate treatment to prevent fractures and preserve bone health.